GENERAL AND SPECIFIC COMBINING ABILITY ANALYSES IN MAIZE UNDER NORMAL AND MOISTURE STRESS CONDITIONS - J. Iqbal; M. Saleem; M. Ahsan; A. Ali (Journal of Animal and Plant Sciences, 2012)
Combining ability analyses are important biometrical tools for evaluation of high yielding maize hybrids to appreciate yield. Present study was conducted to screen out inbred lines for the synthesis of  drought tolerant corn hybrids by manipulating the combining ability analyses techniques in present scenario of diminishing water resources Combining ability estimates were studied by using 6×6 diallel technique in maize crop under normal and moisture stress conditions in the department of Plant Breeding and Genetics, University of Agriculture, Faisalabad during 2008 and 2009.Mean squares due to genotypes, specific and general combining abilities along with reciprocals were found highly significant for all the traits in both conditions. Additive type of gene action was inferred from the values of general and specific combining ability variances. Inbred line “F-206” was found the best general combiner for days to tasseling, silking, maturity and grain yield per plant in both conditions. Maximum GCA effects for plant height were observed in inbred line S-42. Maximum SCA effects for grain yield per plant were expressed in F1 hybrid F-110×F-206 followed by F-192 × F-189 and F-110 × S-42. F-192 × F-206 recombinant was most efficient hybrid for days to maturity. The best  F1 hybrid was F-206 × F-110 followed by F-206 × F-189 ,and S-42× F-206 These F1 hybrids displayed good SCA along with better mean performance for grain yield per plant and most of the traits studied in moisture stress condition. Inbred lines F-206, F-189 and S-42 were the good general combiners for most of the traits. These parents can be involved to produce high yielding and moisture stress tolerant corn hybrids to enhance production in drought prone environment.
Keywords: Zea mays; genotypes; morphological characters; combining ability; moisture stress; Pakistan.